Influence of hydroxyethylstarch solutions on coagulation, blood loss and results of treatment of patients with ischemic heart disease - Gurin, P. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The results of application of colloidal and crystalloid solutions during surgical intervention in patients with coronary heart disease are presented. The influence on the system of coagulation hemostasis of colloidal solutions and related perioperative complications have been investigated. The study included 40 patients operated in A. A. Shalimov National Institute of Surgery and Transplantology about coronary heart disease who performed off-pump coronary bypass grafting surgery (cabg): a study group of 20 patients (in the intraoperative period, solutions of hydroxyethyl starch 130 / 0.4 were used, and a comparison group of 20 patients (only crystalloid solutions were used during the intraoperative period). The results of general and biochemical blood tests, electrolyte, acid-base and gas composition of blood, determined the prothrombin time, the prothrombin index, the international normalized ratio, the active partial thromboplastin time, thromboelastometry indices Statistical analysis of the material was performed using standard methods using the application package “MS Excel” and “StatPlus 2007 Professional”. Estimates of mean, standard errors, reliability of differences.To estimate the difference between groups, parametric t- Investigator’s criterion, when the relationships between the indicators are determined, is a correlation analysis by Pearson. The obtained results have adversely affected the system of coagulation hemostasis of colloidal solutions (changes in the parameters of thromboelastometry, prothrombin time and prothrombin index), and an increase in the frequency of postoperative complications (blood loss, need for blood transfusion, increase in the time of stay in the intensive care unit and in-patient department). The obtained results give prospects for further study of the influence of colloidal solutions on coagulation hemostasis during other surgical interventions (thoracic, abdominal, etc.), as well as the use of the method of thromboelastometry in clinical practice for the early diagnosis of coagulation hemostasis disorders. Keywords: hydroxyethylstarch, off-pump coronary artery bypass grafting surgery, coagulationhemostasis, bloodloss, thromboelastometry, postoperativecomplications.